Changes in cerebral cortex activation during upright standing tasks in individuals with chronic neck pain: an fNIRS study - Xiao, Chongwu; Liang, Qianfei; Yang, Yugang; Mo, Mingyu; Li, Weixiong; Chen, Huade; Long, Yaobin; Huang, Jinjun (Frontiers in Neurology, 2025)
IntroductionStudies show that individuals with chronic neck pain (CNP) exhibit postural control deficits, potentially contributing to persistent and recurrent pain. However, the neural mechanisms underlying these deficits in CNP remain unexplored despite their importance for developing effective rehabilitation strategies. Therefore, this study aimed to investigate the neural activity during postural control using functional near-infrared spectroscopy (fNIRS), providing insights into the central mechanism underlying postural control deficits in individuals with CNP.MethodsIn this cross-sectional study, 10 individuals with CNP (CNP group) and 10 healthy controls (HC group) were assessed under three conditions: Task 1, standing on a force plate with eyes open and both feet; Task 2, standing on a force plate with eyes closed and both feet; Task 3, standing on a force plate with eyes closed and one foot. Cerebral cortex hemodynamic reactions, including bilateral prefrontal cortex (PFC), dorsolateral prefrontal cortex (DLPFC), pre-motor cortex and supplementary motor area (PMC/SMA), primary motor cortex (M1), and primary somatosensory cortex (S1) were measured using fNIRS. Balance parameters, including the sway area, total sway length, mean velocity, and center of pressure (COP) amplitude in the anterior–posterior (AP) and medial-lateral (ML) directions, were measured using a force plate.ResultsIn Tasks 1 and 2, no differences were observed between both groups in balance parameters. However, the CNP group exhibited significantly higher activation in the left PMC/SMA (F = 4.788, p = 0.042) and M1 (F = 9.598, p = 0.006) in Task 1 and lower activation in the left (F = 4.952, p = 0.039) and right (F = 6.035, p = 0.024) PFC in Task 2 compared to that of the HC group. In Task 3, the CNP group exhibited a significantly larger COP amplitude in the AP direction (F = 7.057, p = 0.016) compared to that of the HC group. Additionally, activation in the right M1 (F = 7.873, p = 0.012) was significantly higher than in the HC group. Correlation analysis in Task 3 revealed stronger associations between the parameters in the CNP group.ConclusionOur findings suggest that individuals with CNP exhibit distinct patterns of cerebral cortex activities and postural control deficits. The PFC, M1, and PMC/SMA were involved in maintaining upright standing balance, and cerebral cortex changes associated with upright standing balance provide a more sensitive indicator of postural control deficits than peripheral balance parameters in individuals with CNP.